Das razões da utilização do EBITDA por profissionais de mercado: uma contribuição prática - Carvalho, Vinícius José Ribeiro de (2015)
This study seeks to understand the utilization of EBITDA by Brazilian market professionals. EBITDA, which emerged in the 1970s in the United States as a tool to measure the operating performance of companies with heavy capital investments and / or highly leveraged companies, due to its success quickly spread throughout the world as an important proxy for cash flows. However, over the years the academic and professional community, as well as regulators and standard-setting bodies, raised a number of criticisms and warnings on its use, possibly greater than its virtues. Thus, was born the motivation of this work: why and how highly skilled and qualified professionals continue utilizing EBITDA in their daily work, despite its conceptual weaknesses? Additionally, there was the motivation to discuss an issue lacking depth in Brazil. This is a qualitative and exploratory study, conducted through interviews with a sample of professionals selected by convenience and the data analyzed by the content analysis technique, with ATLAS.ti software support. The results show that the professionals of the sample continue using EBITDA mainly for ease of use and calculation, and deem it a good measure of operating performance. However, in addition to several criticisms, also showed us that they continue to utilize EBITDA due to the lack of a good proxy for cash flow that has a similar cost-benefit relation. Finally, we identified that one of the probable reasons for its mass utilization lies in Mimetic Isomorphism, as analyzed by the New Institutional Sociology, or Neo-institutionalism.